Flow-void and hyperintense vessel sign are unsuitable to characterise a non-vascular stroke-like lesion - Finsterer, Josef (Jour Med Resh and Health Sci, 2021)
With interest we read the article by Chong et al. about a study of 13 patients with mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) and 20 patients with acute ischemic stroke (AIS) for the sensitivity/specificity of the flow-void sign (FVS) and hyperintense vessel sign (HVS) on MRI [1].